Keterkaitan Judi Online dengan Lingkungan Keluarga di Kalangan Remaja Balikpapan - Natavia, Dini Sakti; Haryaka, Usfandi; Sillakhudin, Sillakhudin (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2025)
The development of digital technology has brought major changes to people's lives, including increasing access to online gambling, especially among teenagers. This study aims to analyze the role of the family environment in preventing adolescent involvement in online gambling in Balikpapan. Using a qualitative approach with descriptive methods, this research explores the factors of communication, supervision and emotional support from parents in shaping adolescent behavior towards online gambling. Data was collected through in-depth interviews, observation and documentation, then analyzed using the Miles and Huberman technique. The research results show that open communication within the family, active supervision, and strong emotional support play a significant role in preventing adolescent involvement in online gambling. Conversely, permissive parenting and lack of parental control increase the risk of online gambling addiction. This study highlights the important role of families in creating a conducive environment for adolescent development as well as the need for education for parents in supervising their children's digital activities. The results of this research are also in line with the parenting style theory developed by Baumrind, which distinguishes between authoritative, authoritarian and permissive parenting styles. The implications of this research provide recommendations for stakeholders to strengthen family-based interventions in preventing the negative impacts of online gambling on adolescents